2023
DOI: 10.3390/f14102063
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Diversity and Biomass of Soil Bacteria and Fungi under Different Fire Disturbances in the Taiga Forests of Northeastern China

Zhichao Cheng,
Song Wu,
Jun Du
et al.

Abstract: Fire is a crucial disturbance factor for the structure and function of forest ecosystems, as it directly or indirectly affects plant growth, animal life and soil biogeochemical properties. Here, the effects of different fire severities and key driving environmental factors on soil microbial diversity and biomass were investigated in taiga forests that had undergone light, moderate or heavy fires, more recently or in the past, with unburned taiga forest included as a control (CK). The sample sites were located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Consequently, Acidobacteria and Planctomycetota recovered to pre-fire levels after 6 years. Research has indicated that Chloroflexi exhibits high sensitivity to temperature and a negative correlation with soil temperature [40]. Hence, the impact of fire on Chloroflexi was more pronounced than on Acidobacteria and Planctomycetota, necessitating an extended duration for recovery.…”
Section: Effects Of Fire On Soil Bacterial Communitiesmentioning
confidence: 99%
“…Consequently, Acidobacteria and Planctomycetota recovered to pre-fire levels after 6 years. Research has indicated that Chloroflexi exhibits high sensitivity to temperature and a negative correlation with soil temperature [40]. Hence, the impact of fire on Chloroflexi was more pronounced than on Acidobacteria and Planctomycetota, necessitating an extended duration for recovery.…”
Section: Effects Of Fire On Soil Bacterial Communitiesmentioning
confidence: 99%
“…The study site is located in Huzhong National Nature Reserve, Heilongjiang Province, in China (122 1) and is an area of ongoing investigations in our research group that was recently described in more detail [32]. The area has a cold-temperate continental monsoon climate with marked seasonal temperature differences, with a sudden rise in temperature in spring, a warm and area of ongoing investigations in our research group that was recently described in more detail [32].…”
Section: Location Of the Sample Plotsmentioning
confidence: 99%
“…Daxinganling is the largest distribution area of taiga forests in China, with a monoculture vegetation composition whose tree layer is primarily made up of Larix gmelinii, Betula platyphylla, and Populus davidiana, among which Larix gmelinii is the established species [16]. Soil microbial diversity under different forest types, environmental disturbances, and forest succession in the Greater Khingan Mountains has been studied in recent years [17][18][19].…”
Section: Introductionmentioning
confidence: 99%